الصراع الزعامي بين رمضان السويحلي وعبد النبي بالخير واثره على المقاومه في ليبيا 1912-1931م - عائشة يسمين بوعود; بوعود جميلة; زايد كلثوم (University of Eloued جامعة الوادي, 2025)
شكلت معاهدة أوشي لوزان عام 1912م نقطة تحول حاسمة في تاريخ ليبيا، إذ أفضت إلى انسحاب الدولة العثمانية من طرابلس الغرب وتنازلها عنها لصالح إيطاليا وهذا ما اعتبره الليبيون تخلي السلطة العثمانية عنهم، وفتح الباب واسعا أمام المشروع الاستعماري الإيطالي، ومع بداية الاحتلال واجه الإيطاليون مقاومة شرسة من الليبيين، قادها زعماء بارزون مثل رمضان السويحلي في مصراتة وعبد النبي بلخير في فزان حيث في البداية كانت العلاقة ودية بينهما وكان لهما دور محوري في معركة القرضابية عام 1915م، التي اعتبرت من أبرز ملاحم الجهاد الوطني، غير أن هذه المرحلة لم تخل من التحديات الداخلية، فقد ظهرت خلافات بين قادة المقاومة، لا سيما بين السويحلي وبلخير، نتيجة لاختلاف الرؤى السياسية والانتماءات القبلية، إذ سعى السويحلي إلى إقامة حكم محلي مستقل، بينما مال بلخير إلى سياسة المهادنة وتوازن القوى، وأدت هذه الانقسامات الى اضعاف وحدة المقاومة، ووجدت فيها إيطاليا فرصة لتأجيج النزاع الداخلي عبر سياسة فرق تسد"، ما ساهم في إضعاف جبهة المقاومة في الغرب الليبي، وعلى الرغم من محاولات المخلصين من الوطنيين، كحزب الإصلاح وهيئة الإصلاح، لرأب الصدع وتوحيد الكلمة، إلا أن جهودهم لم تفلح وهكذا، أدى الانقسام الداخلي إلى تراجع زخم الكفاح الوطني، ومنع تشكل جبهة موحدة قادرة على مجابهة الاحتلال الإيطالي بفعالية في تلك المرحلة المصيرية من تاريخ ليبيا. The Treaty of Ouchy-Lausanne in 1912 marked a decisive turning point in Libya's history. It led to the Ottoman Empire's withdrawal from Tripolitania and its ceding it to Italy. Libyans viewed this as an abandonment by the Ottoman authorities, opening the door wide for the Italian colonial project. At the beginning of the occupation, the Italians faced fierce resistance from the Libyans, led by prominent leaders such as Ramadan al-Suwaihli in Misrata and Abd al-Nabi Balkhair in Fezzan. Initially, the relationship between them was friendly, and they played a pivotal role in the Battle of Qardabiya in 1915, which was considered one of the most prominent epics of the national struggle However, this stage was not without internal challenges, as disagreements emerged between the leaders of the resistance. Particularly between al-Suwaihli and Balkhair, this was a result of differing political visions and tribal affiliations. Al-Suwaihli sought to establish independent local rule, while Balkhair favored a policy of appeasement and balance of power. These divisions weakened the unity of the resistance, and Italy saw in them an opportunity to inflame internal conflict through a policy of "divide and conquer." This contributed to the weakening of the resistance. front in western Libya. Despite the attempts of loyal nationalists, such as the Reform Party and the Reform Commission, to mend the rift and unify the position, their efforts were unsuccessful. Thus, the internal division led to a decline in the momentum of the national struggle and prevented the formation of a unified front capable of effectively confronting the Italian occupation at that fateful stage in Libya's history.
مذكرة ماستر تخصص تاريخ العربي المعاصر
Keywords: تغذية الصراع; تأجيج الصراع; المعارك; الصلح; محاولات; الانقسامات الداخلية; الصراع الزعامي; الإنتماءات القبلية; Tribal affiliations; leadership conflict; internal divisions; reconciliation attempts; battles; fueling conflict